2023
DOI: 10.1093/infdis/jiad296
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metagenomic Next-Generation Sequencing of Bronchoalveolar Lavage Fluid on Antimicrobial Stewardship in Patients With Lower Respiratory Tract Infections: A Retrospective Cohort Study

Abstract: Objectives The impact of metagenomic next-generation sequencing (mNGS) on antimicrobial stewardship in patients with lower respiratory tract infections (LRTIs) is still unknown. Methods In this retrospective cohort study, patients diagnosed with LRTIs and underwent bronchoalveolar lavage (BAL) were included between September 2019 to December 2020. Individuals with mNGS and conventional microbiologic tests were classified as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…discovered that incorporating mNGS tests into conventional microbiologic methods was related to lower rates of antibiotic escalation and may potentially aid in cessation of empirical antiviral therapies in lower respiratory tract infections (LRTIs) patients. 22 Meanwhile, mNGS could benefit the patients after allogeneic hematopoietic stem cell transplantation by lowering the mortality of pulmonary complications on account of its early accurate diagnosis and the ability to discern the pathogens. 23 In this study, we evaluated the potential application value of mNGS negative results in patients with corticosteroid-responsive DPLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…discovered that incorporating mNGS tests into conventional microbiologic methods was related to lower rates of antibiotic escalation and may potentially aid in cessation of empirical antiviral therapies in lower respiratory tract infections (LRTIs) patients. 22 Meanwhile, mNGS could benefit the patients after allogeneic hematopoietic stem cell transplantation by lowering the mortality of pulmonary complications on account of its early accurate diagnosis and the ability to discern the pathogens. 23 In this study, we evaluated the potential application value of mNGS negative results in patients with corticosteroid-responsive DPLD.…”
Section: Discussionmentioning
confidence: 99%
“…mNGS reported all the microorganism detected in the sample, encompassing opportunistic pathogen and resident flora in the respiratory tract. 22 Yuan et al. utilize mNGS to uncover the relationship between lung microbiota and lung diseases in patients with pneumoconiosis and pulmonary infection, implying that lung microbiota could be biomarkers in lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The results also showed that mNGS could potentially improve outcomes for patients with LRTIs. Yan et al 12 showed that the use of mNGS was associated with lower rates of antibiotic escalation and may facilitate the cessation of antivirals in patients with LRTIs. Zhao et al 13 demonstrated that the pathogen-positive rate of mNGS in BALF samples was higher than that of culture in patients despite prior antibiotic use, and the results also showed that mNGS of BALF was a potentially useful tool for testing mixed pathogens in severe pneumonia.…”
Section: Introductionmentioning
confidence: 99%